2019
DOI: 10.3389/fphar.2019.00467
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Effects of Acute Aflatoxin B1 Exposure on Hepatic Mitochondrial Lipids and Oxidative Stress in Rats

Abstract: Aflatoxins are secondary metabolites of certain Aspergillus species, that contaminate staple foods, particularly in developing countries. Aflatoxin B1 (AFB1) is the most toxic and common of the major types of aflatoxins. AFB1 is hepatotoxic and has been implicated in increasing the risk of hepatocellular carcinoma (HCC). We have previously shown that subacute exposure to AFB1 for 7 days disrupts hepatic lipids; therefore, this study determined the time-course effects of acute aflatoxin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…Generally, a disruption of the cell membrane can lead to enzymes leaking into the cytosol [ 52 ]. The elevation of plasma activities of these enzymes is part of the diagnosis of liver damage or injury, which has recently been suggested to be caused by biliary cirrhosis, which eventually leads to cholestasis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a disruption of the cell membrane can lead to enzymes leaking into the cytosol [ 52 ]. The elevation of plasma activities of these enzymes is part of the diagnosis of liver damage or injury, which has recently been suggested to be caused by biliary cirrhosis, which eventually leads to cholestasis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…AFB1 acts as a type of human chemical toxicant, and the toxic effects of this toxicant are characterized by organophilism (mainly causing hepatic damage), genic toxicity (mainly inducing DNA damages such as hotspot mutation at codon 249 of TP53 gene, AFB1-DNA adduct formation, and so on), and carcinogenicity (mainly resulting in HCC) [6][7][8]. Among the hepatic toxicity of AFB1, the formation of AFB1-DNA adducts in hepatic cells is a key step during the metabolism of this toxicant [9][10][11][12][13][14]. Evidence from molecular epidemiological studies and clinical studies has proved that the levels of AFB1-DNA adducts in the hepatic tissues are positively associated with the levels and time of AFB1 exposure [3,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…AFB1-induced hepatic effects consist of acute toxic damages (such as severe DNA damage, severe liver degeneration and necrosis, and the failure of hepatic function) and chronic cumulative damages (such as a series of cumulative DNA damage, slight hepatocellular degeneration and necrosis, chronic inflammation, liver cirrhosis, and liver cancer) [3][4][5]. Increasing evidence has shown that under the same exposure of AFB1, some individuals feature severe hepatic damage; others have no noticeable damage [9][10][11][12][13][14]. This suggests that different individuals have different responses to the toxic effects of AFB1 and genetic factors may play a central role in the AFB1-induced hepatic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This epoxide can be involved in enzymatic and non-enzymatic conversion in AFB1-8,9-dixydroxydiol that can bind protein such as albumin, or can be converted in the aflatoxin dialdehyde and excreted via urine as a result of aflatoxin aldehyde reductase action. In the endoplasmic reticulum (ER) of liver cells, AFB 1 is also hydroxylated to fewer toxic metabolites: aflatoxin M 1 (AFM 1 ), aflatoxin Q 1 (AFQ 1 ), and aflatoxin P 1 (AFP 1 ) [59,[64][65][66]. In ruminants fed with contaminated feed, a part of the AFB 1 is degraded by ruminal fluid microbiota and then transformed into an 18-times less toxic metabolite called aflatoxicol.…”
Section: Aflatoxinsmentioning
confidence: 99%